Endolymphatic Sac Drainage Surgery and Plasma Stress Hormone Vasopressin Levels in Meniere's Disease - Kitahara, Tadashi; Okayasu, Tadao; Ito, Taeko; Fujita, Hiroto; Ueda, Keita (Frontiers in Neurology, 2021)
Meniere’s disease is a common inner ear disorder accompanied by vertigo attacks and fluctuating hearing loss that some believe is due to a stressful lifestyle. To elucidate the scientific relationship in neuro-endocrinology between Meniere’s disease and stress, we examined the surgical results of endolymphatic sac drainage surgery and changes in stress-induced plasma arginine-vasopressin levels. We enrolled 100 intractable Meniere’s patients and examined surgical results and plasma vasopressin levels. Fifty-four chronic otitis media patients who underwent tympano-mastoidectomy formed a control group. We assessed surgical results during a 2-year follow-up period, including vertigo and hearing loss. We examined plasma vasopressin levels just before surgery and 1 week, 1 year, and 2 years after surgery. In patients with intractable Meniere’s disease, plasma vasopressin levels were significantly reduced 1 week after surgery compared to the decrease observed in chronic otitis media patients after tympano-mastoidectomy. In intractable Meniere’s disease, long-lasting low plasma vasopressin levels after surgery were associated with significantly good surgical results. In recurrent Meniere’s disease, a gradual plasma vasopressin level elevation was observed after surgery, followed by recurrent vertigo attacks and sensorineural hearing loss. It is suggested that long-lasting high levels of plasma vasopressin could have adverse effects on inner ear water metabolism and the subsequent Meniere’s disease symptoms. Effective treatments for Meniere’s disease might be best based on the maintenance of low plasma vasopressin levels.